IDENTIFYING BANK LENDING CHANNEL IN INDONESIA: A VECTOR ERROR CORRECTION APPROACH WITH STRUCTURAL BREAK - Akhsyim Afandi (Jurnal Keuangan dan Perbankan, 2009)
There was a question whether monetary policy works through bank lending channelrequired a monetary-induced change in bank loans originates from the supply side. Mostempirical studies that employed vector autoregressive (VAR) models failed to fulfill thisrequirement. Aiming to offer a solution to this identification problem, this paper developed afive-variable vector error correction (VEC) model of two separate bank credit markets inIndonesia. Departing from previous studies, the model of each market took account of onestructural break endogenously determined by implementing a unit root test. A cointegrationtest that took account of one structural break suggested two cointegrating vectors identifiedas bank lending supply and demand relations. The estimated VEC system for both marketssuggested that bank loans adjusted more strongly in the direction of the supply equation.